Research on influencing factors of practice effect in educational practice based on the theory of planned behavior - Yu Kang; Lay, Yoon Fah (Human Resource Management Academic Research Society, 2025)
This research investigates and analyzes students' own feelings during educational practice, and explores the relationship among variables such as attitude, subjective norm, perceived behavioral control, participation intention, and practice effect used PLS-SEM, based on the Theory of Planned Behavior. A survey was conducted upon 200 students from three universities, were selected based on purposive and random cluster sampling techniques. Research findings showed that attitude, subjective norm, perceived behavioral control, and participation intention have positive and significant effect on practice effect. Besides, attitude, subjective norm, and perceived behavioral control also showed positive and significant effect on participation intention. Furthermore, one sub-dimension of participation intention showed mediating effect for the relationship between attitude on the practice effect, and another sub-dimension of participation intention showed mediating effect in the relationship between subjective norm and practice effect, as well as perceived behavioral control and practice effect in educational practice. Through the in-depth research of the practice effect in educational practice, it can provide scientific basis for the reform and development of teacher education, so as to better train excellent teachers to meet the needs of modern education.